An experimental investigation of a laminar separation bubble on the leading-edge of a modelled aerofoil for different Reynolds numbers. (August 2016) - Samson, A; Sarkar, S
This paper describes the dynamics of a laminar separation bubble formed on the semi-circular leading edge of constant thickness aerofoil model. Detailed experimental studies are carried out in a low-speed wind tunnel, where surface pressure and time-averaged velocity in the separated region and as well as in the downstream are presented along with flow field visualisations through PIV for various Reynolds numbers ranging from 25, 000 to 75, 000 (based on the leading edge diameter). The results illustrate that the separated shear layer is laminar up to 20% of separation length and then the perturbations are amplified in the second half attributing to breakdown and reattachment. The bubble length is highly susceptible to change in Reynolds number and plays an important role in outer layer activities. Further, the transition of a separated shear layer is studied through variation of intermittency factor and comparing with existing correlations available in the literature for attached flow and as well as separated flow. Transition of the separated shear layer occurs through formation of K-H rolls, where the intermittency following spot propagation theory appears valid. The predominant shedding frequency when normalised with respect to the momentum thickness at separation remains almost constant with change in Reynolds number. The relaxation is slow after reattachment and the flow takes about five bubble lengths to approach a canonical layer.